Communications In the Media Management System - Hujanova Mastura Ibodullaevna (Genius Journals, 2021)
The article deals with communication in the media management system in modern time. In the development of periodicals in our country over the past decade, important processes have taken place and are taking place today, which have had a significant impact on the practice of world information exchange. Among their reasons, it is possible to single out, first of all, a set of cardinal changes associated with changes in technologies for receiving, processing, storing and transmitting information products, the development of Internet communications, as well as those caused by globalization trends.
Keywords: Communications; Information Transfer; Information Reality; Telecommunication Networks